KOMBINASI STRETCHING ACTIVE DAN BRISK WALKING TERHADAP PENURUNAN TEKANAN DARAH KLIEN HIPERTENSI - Ida Suryati; Dia Resti Dewi Nanda Demur; Ririn Khairina (JURNAL KESEHATAN PERINTIS, 2017)
This research was motivated by teh increasing of hypertension accidents.In 2013 patient hypertension as many as 168 people, 2014 increased 190 people and 2015 as many as 225. One of the non pharmacological managements of patient hypertension is activity excercise. Activity excersise is recomended for patients with hypertension is stretching active and brisk walking which can decrease blood pressure the patient. The purpose of this study was to determine the effect of the combination of active stretching and brisk walking to the decrease in blood pressure. This research method was quasi experimental design with one group pretest-posttest. Intervention in the form of implementation of active stretching and brisk walking for 2 weeks. The study sample as many as 19 people in Puskesmas Plus Mandiangin London in 2016. The results show that there is the influence of a combination of active stretching and brisk walking to the decrease in blood pressure. Results Wilcoxon Signed Rank Test showed the difference in systolic and diastolic pressure before and after the intervention (p = 0.000). The average difference in systolic blood pressure measurements pre-post is (20.526 ± 12.236). And the average difference in diastolic blood pressure measurements pre-post is (12.632 ± 5.620). This study concludes that significantly active stretching and brisk walking can lower blood pressure in hypertensive patients.